2023
DOI: 10.1146/annurev-environ-112621-063400
|View full text |Cite
|
Sign up to set email alerts
|

Metrics for Decision-Making in Energy Justice

Erin Baker,
Sanya Carley,
Sergio Castellanos
et al.

Abstract: Energy equity and justice have become priority considerations for policymakers, practitioners, and scholars alike. To ensure that energy equity is incorporated into actual decisions and analysis, it is necessary to design, use, and continually improve energy equity metrics. In this article, we review the literature and practices surrounding such metrics. We present a working definition for energy justice and equity, and connect them to both criteria for and frameworks of metrics. We then present a large sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Recent reviews have highlighted that research on equity and charging infrastructure has to date focused predominantly on questions of placement (Kontou et al 2022, Carlton and Sultana 2023, Hopkins et al 2023 and distribution (Baker et al 2023). By drawing on grey literature and news reports, in addition to academic literature, we identify additional dimensions of charging equity that we argue are important to consider in charging infrastructure planning and research.…”
Section: A Framework For Assessing Equity In Public Charging Infrastr...mentioning
confidence: 99%
“…Recent reviews have highlighted that research on equity and charging infrastructure has to date focused predominantly on questions of placement (Kontou et al 2022, Carlton and Sultana 2023, Hopkins et al 2023 and distribution (Baker et al 2023). By drawing on grey literature and news reports, in addition to academic literature, we identify additional dimensions of charging equity that we argue are important to consider in charging infrastructure planning and research.…”
Section: A Framework For Assessing Equity In Public Charging Infrastr...mentioning
confidence: 99%
“…Increased electrification is necessary for incorporating more renewables in the energy mix, while sectors which cannot easily be electrified are considered "hard-to-abate" (Paltsev et al, 2021). Energy Burden is calculated in each region as per capita spending on residential energy use divided by per capita GDP, and is a widely used metric for energy equity and energy justice considerations (Baker et al, 2023). Capacity Investments and Stranded Assets are economic metrics reporting the costs of new capacity additions and premature capacity retirements in the power sector, respectively, due to implementing climate pledges (Binsted et al, 2020;Iyer et al, 2015b;Zhao et al, 2021).…”
Section: Output Metricsmentioning
confidence: 99%
“…Energy justice scholars have described important dimensions of equity including health, access, and livelihood, and have suggested that key components of an equitable energy transition include renewable energy deployment, fossil fuel infrastructure retirement, transportation electrification, and residential building decarbonization [10]. Others have suggested additional dimensions including consumer energy consumption, wealth creation, ownership, and autonomy; multi-scalar supply chain equity; and comparative country-level equity [11].…”
Section: Introductionmentioning
confidence: 99%